RAUDHOH SEBAGAI KONSEP INNER PEACE: ANALISIS SEMANTIK AL-QUR’AN DALAM KONTEKS KESEHATAN MENTAL - Muhammad Fajar (Dirasat: Journal Islamic Studies, 2025)
This research was conducted against the background of increasing psychological distress in adolescents and college students that affects their mental health, especially related to stress and anxiety. Previous findings show a complex relationship between psychological factors, lifestyle, and resilience in forming a stable mental state. The urgency of this research lies in the need to understand the concept of inner peace based on the Qur'an, which can be a reference for psychological interventions based on spiritual values. The purpose of the research is to map the network of meanings of the word raudhoh in the Qur'an to understand the representation of inner peace, as well as to compare the historical meaning of the pre-Qur'an with the spiritual meaning in the sacred text. The research uses a qualitative method with an interpretive paradigm through encyclopedic semantic analysis. Data was collected from Qur'anic verses containing the word raudhoh, tafsir studies, and classical linguistic sources, then analyzed through concept extraction, meaning relationship mapping, and conceptual interpretation. The results of the study show that raudhoh in the pre-Qur'an period refers to a fertile, watery, and soothing physical space, while in the Qur'an it has been transformed into a symbol of spiritual enjoyment, peace of mind, and retribution for believers. Relational analysis confirms that raudhoh represents five aspects of inner serenity: inner fertility, acceptance, emotional balance, meaning of life, and spiritual well-being. In conclusion, raudhoh is not just a physical place, but an image of inner peace that is integrated in the spiritual and psychological experience of humans, providing a new perspective for strengthening mental health based on the values of the Qur'an.